ALS drug development guidances and trial guidelines: Consensus and opportunities for alignment. (9th July 2019) - Andrews, Jinsy A.; Bruijn, Lucie I.; Shefner, Jeremy M.
Abstract : The US Food and Drug Administration (FDA) developed a draft guidance for drug development in amyotrophic lateral sclerosis (ALS) that was issued in February 2018. The FDA draft guidance considered the recommendations developed by the ALS community that incorporated the views of a large group of clinical investigators, industry representatives, advocacy groups, patients, and caregivers. This external input from the ALS community reviewed the current state of clinical research in ALS, made suggestions over a wide range of drug development topics, and served as an educational tool to provide the agency with additional inputs about ALS, the state of the science, and the community's views on key topics. In parallel to this effort, there was an independent effort to revise and update the ALS Clinical Trial Guidelines. We discuss the areas of agreement of these 3 documents and the areas that provide opportunities to improve the efficiency of drug development in ALS. It is likely that further research into biomarkers, efficacy endpoints, and predictive algorithms will provide greater alignment among community stakeholders and increase clarity on drug development efforts going forward. Continued patient engagement and inclusion of patient experience data in every aspect of the drug development process will further facilitate the approval of new treatments.